(3GdHMQ GdRGNQ ajeG bGdg SYO Hf Ydj GdTGYQ GdegfOjs - (3SYO Hf Ydj GdTGYQ, cGf MjG (B1333(3g`s ((3bWQs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejfCeG HYO abO WdHfj HYV GdeMHjf Cf CLeY OjhGfG ef bUGFO GdeQMhe SYO Hf Ydj GdTGYQ GdegfOj hHYV eG fMVQg ef bUGFO ZjQg ef GdTYQ aCLHJg dPdc hSejJg GdHMQ GdRGNQ ajeG bGdg SYO Hf Ydj GdTGYQs
(3BNQgG (B:s
(3WhdG HeYGfj SjOj YfO YOgG (B*** (3hQOO Ydi hGaj GdNUGd KfGg , ahRG HcQG eGJg Ydi cd ef YWG (B*** (3ebGYO jROhfj hLGg hLGgs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdCOHs